Solving Neutrosophic Travelling Salesaman Problem in Triangular Fuzzy Number Using Ones Assignment Method - Subasri , S. (International Journal of Psychosocial Rehabilitation, 2020)
Travelling salesman problem is awell-known studied problem and intensely used in computational mathematics and management studies. In this paper we discuss a Neutrosophictriangular fuzzy numbers which are more realistic in nature. Neutrosophic triangular fuzzy numbers can converted to a Neutrosophic fuzzy numbers by using a Pascal’s graded mean approach and then the problem is solved by ones assignment method. Neutrosophic crisp travelling salesman problem also solved by using a score function and finally find the optimality. Numerical examples are included for a fruitful way.